2009
DOI: 10.1007/s10336-008-0368-9
|View full text |Cite
|
Sign up to set email alerts
|

High mortality and sex ratio imbalance in a critically declining Oriental White-backed Vulture population (Gyps bengalensis) in Pakistan

Abstract: Populations of Oriental White-backed Vulture (Gyps bengalensis) and Long-billed Vulture (Gyps indicus) declined dramatically by 95-100% on the Indian subcontinent in during the mid-1990s. The study reported here was conducted in Pakistan to compare the population size, breeding success, patterns of mortality and sex ratios among dead vultures and newly hatched nestlings of G. bengalensis and G. indicus at Toawala (TW) and Nagar Parkar (NP), respectively, during the breeding seasons 2005/2006 and 2006/2007. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Mortalities in our study were caused by visceral gout caused by diclofenac residues in livestock carcasses (Arshad et al 2009), which was a primary food source for our study population. Interviews with livestock and veterinary officers in Nagar Parkar indicated that diclofenac was commonly used to treat livestock in the area (Chaudhry 2004(Chaudhry , 2009.…”
Section: Discussionmentioning
confidence: 87%
“…Mortalities in our study were caused by visceral gout caused by diclofenac residues in livestock carcasses (Arshad et al 2009), which was a primary food source for our study population. Interviews with livestock and veterinary officers in Nagar Parkar indicated that diclofenac was commonly used to treat livestock in the area (Chaudhry 2004(Chaudhry , 2009.…”
Section: Discussionmentioning
confidence: 87%
“…Restrictions on the size of vials of injectable human diclofenac to make it less easy to use human formulations on livestock may help to eliminate these illegal practices. A similar situation may also exist in the Punjab province of Pakistan, where diclofenac-caused mortality of oriental white-backed vultures continued after government action to prevent its veterinary use [19]. If the recovery of wild vulture populations is to be achieved, additional efforts are needed to complete the removal of diclofenac from their food supply and to prevent its replacement by other lethal NSAIDs such as ketoprofen [14], [20].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, the environmental presence of diclofenac has been associated with the devastation of different species and populations of vultures (Arshad et al 2009). Toxicological effects of diclofenac on riparian and aquatic biota must be assessed either pure or in mixture with other pharmaceuticals with which synergistic effects could result (Cleuvers 2003).…”
Section: Introductionmentioning
confidence: 99%